1994
DOI: 10.1093/oxfordjournals.aje.a117000
|View full text |Cite
|
Sign up to set email alerts
|

Energy Adjustment Methods for Nutritional Epidemiology: The Effect of Categorization

Abstract: The authors discuss the interpretation of four alternative energy adjustment methods (Residual, Standard, Partition, and Nutrient Density) that have been proposed for the analysis of nutritional epidemiology studies. These methods have so far been compared under circumstances where intake of the nutrient of interest is measured as a continuous variable. Because it is common practice to categorize nutrient intakes in the analysis, the authors investigate the effect of such categorization on the interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 0 publications
0
67
0
Order By: Relevance
“…This theory is based on the assumption of using nutrient intake as a continuous variable. It is however common practice to categorise nutrient intakes, which removes the equivalencies between models (Brown et al, 1994;Willett et al, 1997). It has been observed that, when nutrient intake is expressed as categories, risk estimates from the nutrient residual and the nutrient density models become similar (Decarli et al, 1997;Kushi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This theory is based on the assumption of using nutrient intake as a continuous variable. It is however common practice to categorise nutrient intakes, which removes the equivalencies between models (Brown et al, 1994;Willett et al, 1997). It has been observed that, when nutrient intake is expressed as categories, risk estimates from the nutrient residual and the nutrient density models become similar (Decarli et al, 1997;Kushi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Natural logarithmic transformation was applied for plasma folate and tHcy, and folate and energy intakes because these variables had a skewed distribution and the transformation improved the normality of the distribution. Folate intake was adjusted for energy intake by using the residual method (32 into the regression model and examined the significance of coefficients of the interaction term. To examine the associations among those with high risk levels of tHcy, we also performed similar analyses restricting subjects to those with tHcy levels higher than the reference range (13.5 nmol/mL, n520).…”
Section: Methodsmentioning
confidence: 99%
“…We also adjusted for menopausal status (pre or post) and current use of female hormones (user or nonuser) in women only. Each dietary factor was adjusted by total energy with the use of the residual method (33)(34)(35) into the statistical model after log transformation. Isoflavone, miso soup, and soy food consumption were not included in the same models due to colinearity.…”
Section: Methodsmentioning
confidence: 99%